Measurement of information technology governance capability level: a case study of PT Bank BBS - Punto Widharto; Zaldy Suhatman; Rizal Fathoni Aji (Universitas Ahmad Dahlan, 2022)
The very close involvement of technology in the banking industry makes almost all banking activities and products currently dependent on information technology (IT). PT BPRS Bhakti Sumekar (PT BBS Bank) is one of the banks that realizes the importance of IT in the digital era and has included IT as part of the company's strategic plan. The company states that compliance with regulations, best practices, and standards is key to a successful IT implementation. In this study, the measurement of the capability level of corporate IT governance was conducted to determine what IT priorities were based on the company's strategic objectives and what recommendations could be given based on best practices to improve IT services in support of the company's strategic goals. The framework to be used is control objective for information and related technology (COBIT); the most widely used framework suitable for service-oriented organizations. The results of research using COBIT 2019 show how IT governance is needed by the company and what should be prioritized. The measurement results found that there is still a gap between management's expectations and the current level of capability and provide recommendations on what companies need to improve performance in order to meet expectations.